Effects of geohelminth infection and age on the associations between allergen‐specific IgE, skin test reactivity and wheeze: a case‐control study. Issue 1 (24th December 2012) - Moncayo, A.‐L.; Vaca, M.; Oviedo, G.; Workman, L. J.; Chico, M. E.; Platts‐Mills, T. A. E.; Rodrigues, L. C.; Barreto, M. L.; Cooper, P. J.
Summary Background Most childhood asthma in poor populations in Latin America is not associated with aeroallergen sensitization, an observation that could be explained by the attenuation of atopy by chronic helminth infections or effects of age. Objective To explore the effects of geohelminth infections and age on atopy, wheeze, and the association between atopy and wheeze. Methods A case‐control study was done in 376 subjects (149 cases and 227 controls) aged 7–19 years living in rural communities in Ecuador. Wheeze cases, identified from a large cross‐sectional survey, had recent wheeze and controls were a random sample of those without wheeze. Atopy was measured by the presence of allergen‐specific IgE (asIgE) and skin prick test (SPT) responses to house dust mite and cockroach. Geohelminth infections were measured in stools and anti‐Ascaris IgE in plasma. Results The fraction of recent wheeze attributable to anti‐Ascaris IgE was 45.9%, while those for SPT and asIgE were 10.0% and 10.5% respectively. The association between atopy and wheeze was greater in adolescents than children. Although Anti‐Ascaris IgE was strongly associated with wheeze (adj. OR 2.24 (95% CI 1.33–3.78, P = 0.003) and with asIgE (adj. OR 5.34, 95% CI 2.49–11.45, P < 0.001), the association with wheeze was independent of asIgE. There was some evidence that the association between atopy and wheeze was greater in uninfected subjects compared with those with active geohelminth infections. Conclusions and clinical relevance Atopy to house dust mite and cockroach explained few wheeze cases in our study population, while the presence of anti‐Ascaris IgE was an important risk factor. Our data provided only limited evidence that active geohelminth infections attenuated the association between atopy and wheeze in endemic areas or that age modified this association. The role of allergic sensitization to Ascaris in the development of wheeze, independent of atopy, requires further investigation.